2017
DOI: 10.1002/bem.22062
|View full text |Cite
|
Sign up to set email alerts
|

Biological effects related to geomagnetic activity and possible mechanisms

Abstract: This review presents contemporary data on the biological effects of geomagnetic activity. Correlations between geomagnetic indices and biological parameters and experimental studies that used simulated geomagnetic storms to detect possible responses of organisms to these events in nature are discussed. Possible mechanisms by which geomagnetic activity influences organisms are also considered. Special attention is paid to the idea that geomagnetic activity is perceived by organisms as a disruption of diurnal ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 109 publications
0
29
0
1
Order By: Relevance
“…It is, however, still possible that dunnocks and chiffchaffs pay less attention to geomagnetic cues, or use alternative cues, for orientation on migration [4]. Future studies should investigate the importance of geomagnetic when compared with celestial cues for orientation in both diurnal and nocturnal bird migrants, and systematically investigate how the temporal components of magnetic storms [2] affect birds' behaviour. Focusing on a single target species, it would be possible to increase the sample size and using alternative analysis procedures measure other behavioural features, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is, however, still possible that dunnocks and chiffchaffs pay less attention to geomagnetic cues, or use alternative cues, for orientation on migration [4]. Future studies should investigate the importance of geomagnetic when compared with celestial cues for orientation in both diurnal and nocturnal bird migrants, and systematically investigate how the temporal components of magnetic storms [2] affect birds' behaviour. Focusing on a single target species, it would be possible to increase the sample size and using alternative analysis procedures measure other behavioural features, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The Sun's energy flux shows periodic variations with longer intervals of low energy and shorter intervals with high energy that are defined as solar storms [1]. The high-energy ions emitted during solar storms interact with the ionosphere causing temporary alterations of the geomagnetic field with stronger effects at higher latitudes [1,2]. Songbirds possess the ability to detect and use the geomagnetic field for orientation during migration [3,4], but it is not clear if they are able to tell apart the spatial characteristics and the temporal variations of the magnetic field [5].…”
Section: Introductionmentioning
confidence: 99%
“…Prompted by their putative role in magnetoreception, cryptochromes have become the focus of recent discussions of fortuitous radical pair effects in biology (31)(32)(33)(34)(35)(36)(37)(38)(39). Juutilainen et al, for example, have proposed a hypothesis to explain the link between environmental ELF magnetic fields and childhood leukaemia ('magnetocarcinogenesis') (12).…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that weak magnetic fields influence the state of radical pairs at electron transfer between cryptochrome and tryptophan residuals [Hore and Mouritsen, 2016; Solov'yov et al, 2007]. Some researchers suppose that these processes could be responsible for the biological effects of geomagnetic activity [Close, 2012; Krylov, 2017; Vanderstraeten et al, 2015]. In addition, the synthesis of known mammalian circadian hormone melatonin in crustaceans also occurs in a diurnal manner and is involved in regulation of reproduction [Sainath et al, 2013].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the analysis of experimental data [Krylov et al, 2014; Martinez‐Breton and Mendoza, 2016; Gurfinkel et al, 2018] and the correlations between geomagnetic indices and biological processes [Chernouss et al, 2001; Gmitrov and Gmitrova, 2004; Azcaratea et al, 2016], it was previously suggested that geomagnetic storms could be perceived by organisms as a distortion of diurnal geomagnetic variation [Krylov, 2017; Krylov et al, 2019]. In other words, the inconsistency of circadian biochemical processes synchronized with light regime and diurnal geomagnetic variation may be responsible for the medical and biological effects of geomagnetic storms.…”
Section: Introductionmentioning
confidence: 99%